Multivalent meningococcal serogroup B vaccines: challenges in predicting protection and measuring effectiveness. (September 2015) - Poolman, Jan T; Richmond, Peter
<x xml:space="preserve">Abstract</x> Vaccines targeting Neisseria meningitidis serogroup B (MenB) have been attempted for 40 years. Monovalent outer membrane vesicle vaccines targeted at epidemic outbreaks have been successfully developed. Newer vaccines aim to induce antibodies to cross-reactive antigens, such as factor H binding protein (rLP2086) or a mix of outer membrane vesicle, factor H binding protein and other minor antigens (4CMenB). The true protective coverage among circulating MenB isolates afforded by these vaccines is unknown. Carefully conducted Phase IV post-implementation evaluations designed to measure specific effectiveness against major circulating MenB clonal lineages are needed to address the critical question of which antigens are linked to protection. Progress with whole-genome sequencing and bio-informatics may allow the composition of antigen mozaics based on two major outer membrane proteins: PorA and FetA.